HUBUNGAN TINGKAT PENDIDIKAN TERHADAP PARTISIPASI PETANI DALAM SAPTA USAHA TANI DI DESA KEBONHARJO, KECECAMATAN PATEBON, KABUPATEN KENDAL TAHUN 2014 (Edu Geography, 2015)
PenelitianÂ  iniÂ Â  bertujuanÂ  untukÂ  mengetahuiÂ  mengetahuiÂ  tingkatÂ  pendidikan, partisipasi masyarakat dalam sapta usaha tani dan hubungan antara tingkat pendidikan dengan partisipasi masyarakat dalam sapta usaha tani di Desa Kebonharjo,Â Â  Kec.Â Â  Patebon,Â  Kab.Â  Kendal.Â  MetodeÂ Â  yangÂ Â  digunakanÂ Â  adalah deskriptif kuantitatif dengan teknik pengumpulan data melalui angket. Hasil penelitianÂ Â  adalahÂ Â  (1)Â Â  TingkatÂ Â  pendidikanÂ Â  masyarakatÂ Â  petaniÂ Â  denganÂ Â  nilai prosentase sebesar 50% (2) Partisipasi masyarakat petani dalam sapta usaha tani dengan nilai prosentase sebesar 52,8%Â Â Â  (3) Hasil perhitungan dengan menggunakan statistik korelasi product moment taraf signifikansi 5%, diperoleh hasil rxy sebesar 0,505 sedangkan r tabel dengan 0,312. Karena nilai r hitung > r tabel (0,519 > 0,312) maka HaÂ  yang berbunyi â€œada hubungan antara tingkat pendidikan dengan partisipasi masyarakat dalam program sapta usaha tani di desa Kebonharjoâ€.Â  TerdapatÂ  hubunganÂ  yangÂ  signifikanÂ  antaraÂ  tingkatÂ  pendidikan dengan partisipasi masyarakat dalam program sapta usaha tani.Â ThisÂ  studyÂ  aimsÂ  toÂ  determineÂ  determineÂ  theÂ  levelÂ  ofÂ  education,Â  community participationÂ  in farming andÂ  the relationship betweenÂ  levelÂ  ofÂ  educationÂ  and community participation in Kebonharjo farming village, districts Patebon, district Kendal. The method used is descriptive quantitative techniques of data collection through questionnaires. The results of the study are (1) the educational attainment farmingÂ  community withÂ  aÂ  percentage valueÂ  ofÂ  50%Â  (2) participationÂ  by the farmers in farming Sapta with the percentage of 52,8% (3) Results of statistical calculations using product moment correlation, rxy results obtained by 0.519 while the table with 0,312 r. Because r hitung > r tabel (0.505> 0.312), the Ha which reads "there is a relationship between level of education and community participation in the program Sapta Kebonharjo farm in the village". There is a significant relationship between level of education and community participation in the farming. This study aims to determine determine the level of education, community participation in farming and the relationship between level of education and community participation in Kebonharjo farming village, districts Patebon, district Kendal. The method used is descriptive quantitative techniques of data collection through questionnaires. The results of the study are (1) the educational attainment farming community with a percentage value of 50% (2) participation by the farmers in farming Sapta with the percentage of 52,8% (3) Results of statistical calculations using product moment correlation, rxy results obtained by 0.519 while the table with 0,312 r. Because r hitung > r tabel (0.505> 0.312), the Ha which reads "there is a relationship between level of education and community participation in the program Sapta Kebonharjo farm in the village". There is a significant relationship between level of education and community participation in the farming.